Pre- and post-COVID-19 pandemic identification of dengue hotspots and exploration of population and environmental determinants of dengue in Quezon City, Philippines - John Robert Carabeo Medina; Shin’ya Kawamura; Rie Takeuchi; Rolando V. Cruz; Johnedel Mendoza; Paul Michael R. Hernandez; Fernando B. Garcia; Ernesto R. Gregorio; Jun Kobayashi (Tropical Medicine and Health)
Abstract In 2020, there were decreasing trends in reported dengue cases in several countries in the Western Pacific Region, including the Philippines, amid the COVID-19 pandemic. In this study, the spatial distribution of dengue incidence and the hotspots were described quarterly in Quezon City from 2019 to 2022, with the unit of analysis being the 142 barangays (small territorial and administrative villages) in Quezon City. The influence of selected environmental and demographic factors on the persistence of dengue was also explored. Surveillance data from the Quezon City Epidemiology and Surveillance Division, Normalized Difference Vegetation Index (NDVI), and satellite images of built environments, such as buildings, facilities, and transportation network hubs were processed and analyzed. The local Moran’s I statistics performed with 95% confidence level was employed in the identification of local dengue hotspots. Dengue hotspot maps and maps of greenness, surrounding greenness, small building ratios, and the number of transportation network hubs in each barangay (village) of Quezon City were developed. The association of dengue cases with greenness, surrounding greenness, transportation network hubs, small building ratios, and population density was determined through a generalized linear model (GLM). Results revealed that incidence rates of dengue across barangays were spatially heterogeneous, and the dengue hotspots were unstable as they varied quarterly each year. Proximity to surrounding greenness (NDVI 1 km), small building ratio, and presence of transportation network hubs were found to be significantly associated with dengue hotspots. Dengue prevention strategies, such as search-and-destroy activities for breeding sites, are suggested to be implemented regularly in such areas. The study also recommends considering the anticipated increase in dengue hotspots and the significant environmental factors in the development of health promotion and education campaigns.